An MRI Study on Effects of Math Education on Brain Development Using Multi-Instance Contrastive Learning - Zhang, Yupei; Liu, Shuhui; Shang, Xuequn (Frontiers in Psychology, 2021)
This paper explores whether mathematical education has effects on brain developments from the perspective of brain MRIs. While biochemical changes in the left middle front gyrus region of the brain had been investigated, we proposed to classify students by using MRIs from the intraparietal sulcus (IPS) region that was left no touch in the previous study. On the cropped IPS regions, the proposed model develops popular contrastive learning (CL) to solve the problem of multi-instance representation learning. The resulted data representations are then fed into a linear neural network to identify the student into the math group or the non-math group. Experiments were conducted on 123 adolescent students, including 72 math students and 51 non-math students. The proposed model achieved an accuracy of 90.24 % for student classification, gaining more than 5% improvements compared to the classical CL frame. Our study provides not only a multi-instance extension to CL and but also an MRI insight into the impact of Mathematical studying on brain developments.